0531 Characterization of Sleep-Disordered Breathing among Newborn Infants with Myelomeningocele. (25th May 2022) - Hassan, Fauziya; Mason, Thornton; McCaffery, Harlan; Chervin, Ronald; Shellhaas, Renee
Abstract: Introduction: Myelomeningocele (MMC) is a neural tube defect associated with hindbrain herniation (Chiari II malformation) and respiratory center dysfunction. Prior cross-sectional polysomnographic studies indicated that older children with MMC have an elevated risk of sleep-disordered breathing (SDB), a risk factor for sudden death. Most infants with MMC (78%) had abnormal pneumograms, reported predominantly as central sleep apnea (CSA) and sleep-related hypoventilation (SRH). Pneumograms, however, have significant limitations compared with full polysomnography (PSG). Methods: The North-American Fetal Therapy Network (NAFTNet) with nine participating sites has collaborated in a prospective study of SDB among infants with MMC. Bedside PSGs were conducted among infants >35 weeks post-menstrual age without supplemental oxygen or respiratory support. PSGs were scored by a pediatric-experienced RPSGT using the American Academy of Sleep Medicine infant sleep staging and pediatric scoring criteria for respiratory events. PSGs were reviewed independently by two board-certified pediatric sleep faculty who then reached diagnostic consensus. Results: Twenty-eight PSGs were evaluated as an interim analysis from 4 of 9 participating sites. Many (11/28, 39.3%) infants had predominantly frequent hypopneas, which could not be distinguished confidently as central vs. obstructive by two experienced pediatric physicians. The proportions of neonates with CSA (3/28, 10.7%), OSA (6/28, 21.4%) and SRH (1/28, 3.6%) were small by comparison. Only 10/28 infants (35.7%) did not display significant SDB and 14/28 had PSG abnormalities considered clinically concerning. Across all subjects the median [IQR] hypopnea index was 18 [10, 33], central apnea index was 4 [1, 7]) and obstructive apnea index was 1.0 [0, 6]. The median [IQR] apnea-hypopnea index was 28 [15, 46]. Conclusion: This ongoing study already provides the largest available cohort of neonates with MMC and PSG data. Predominant hypopneas were far more common than any other classified expression of SDB and were challenging to distinguish as central or obstructive. These data confirm the high frequency of SDB in MMC (64%), suggest that PSG may be an important consideration in neonates with MMC, but highlight that current scoring criteria may not always allow confident separation of central from obstructive SDB processes. Support (If Any): National Institutes of Health 1 R01 HL147261-01A1